2004
DOI: 10.1161/01.cir.0000109496.82683.49
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Strategy to Treat Brain Ischemia

Abstract: Background-Although cerebral occlusive disease leads to cerebral ischemic events, an effective treatment has not yet been established. An ideal therapeutic approach to treat ischemia might have both aspects of enhancement of collateral formation and prevention of neuronal death. Hepatocyte growth factor (HGF) is a potent angiogenic factor that also acts as a neurotrophic factor. Thus, in this study, we examined the therapeutic effects of HGF on brain injury in a rat permanent middle cerebral artery occlusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 46 publications
4
46
0
Order By: Relevance
“…Both of them showed significant improvement of neurological deficits compared with MSC-only cell therapy. We got the same result as that Shimamura et al (2004) had reported, that HGF had the therapeutic efficiency of reducing the infarction volume after transient MCAO. We also found on day 14 that the MSC-only treated group could significantly reduce the infarction volume under the superacute treatment compared with the PBS-treated group, but not under the acute treatment.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Both of them showed significant improvement of neurological deficits compared with MSC-only cell therapy. We got the same result as that Shimamura et al (2004) had reported, that HGF had the therapeutic efficiency of reducing the infarction volume after transient MCAO. We also found on day 14 that the MSC-only treated group could significantly reduce the infarction volume under the superacute treatment compared with the PBS-treated group, but not under the acute treatment.…”
Section: Discussionsupporting
confidence: 82%
“…So far, to reduce the disability resulting from stroke, some studies have focused on the development of neuroprotective agents such as brainderived neurotrophic factor, the fibroblast growth factor that effectively prevents delayed neuronal death after transient brain ischemia (Kurozumi et al, 2004;Watanabe et al, 2004). Recently, overexpression of HGF that can improve the neurological sequalae by neuroprotection, reduce the infarct volume, and the likelihood of brain edema after stroke was reported (Miyazawa et al, 1998;Tsuzuki et al, 2000;Hayashi et al, 2001;Shimamura et al, 2004). It suggested that HGF should be one of the most potent growth factors for treating brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restored perfusion in the expanded ischemic border area ( Figure 4F) appeared to be connected with the promotion of collateral flow, which enhances the recovery of blood flow in ischemia-affected tissue ( Figure 6A). The restored perfusion may prevent continuing cell death and promote neural plasticity in a neuroprotective microenvironment, since neurons are highly sensitive to hypoxia-ischemia (Shimamura et al, 2004). Finally, early elimination of edema in the lesion boundary area, which was associated with significant reduction of relaxation times (Figures 5B and 5C in pseudo-normal area), may also contribute to the rescue of tissue from ongoing damage.…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, Evans blue dye (Sigma-Aldrich Inc., St Louis, MO, USA, 2% in saline, 3 mL/kg) was injected via the femoral vein under pentobarbital anesthesia (65 mg/kg, intraperitoneally) 1 day after ischemic insult (Shimamura et al, 2004). One hour after the injection, the rats were anesthetized with pentobarbital (overdose, intraperitoneally) and perfused transcardially with physiologic saline.…”
Section: Evaluation Of Blood-brain Barrier Permeabilitymentioning
confidence: 99%